Optimization of Pellets Containing Solid Dispersion Prepared by Extrusion/Spheronization Using Central Composite Design and Desirability Function - Singh, Gurinder (Medknow Publications & Media Pvt Ltd, 2012)
Furosemide is a class IV biopharmaceutical classification system drug having poor water solubility and low bioavailability due to the hepatic first-pass metabolism and has a short half-life of 2 h. To overcome the above drawback, this study was carried to prepare and evaluate the pellets containing furosemide solid dispersion (SD) for oral administration prepared by extrusion/spheronization. SD of furosemide was prepared with Eudragit L-100 at a drug-to-polymer ratio of 1:2 by employing a solvent evaporation method and characterized. Further, microcrystalline cellulose pellets containing SD were consequently prepared using a lab scale extrusion/ spheronizer and evaluated for in vitro drug release studies. The influence of process parameters used during extrusion/spheronization on the pellet properties was also studied using 2-factor, 3-level central composite design in order to improve the product quality. Additionally, the desirability function approach was applied to acquire the preeminent compromise between the multiple responses. Pellets containing solid dispersion (PSD) were prepared using optimal parameter settings demonstrated 88.52 ± 0.69% of the drug was released in a sustained release manner till 12 h. In vitro drug release data were fitted to various release kinetics models to study the mechanism of drug release. Drug release from the PSD was found to follow zero-order and Higuchi's model. Both studied parameters had great influence on the responses. PSD showed augmentation in the drug release profile till 12 h. The final optimized formulation was obtained by encapsulating best SD formulation within the pellet core to release the drug in the most soluble form in stomach and a sustained fashion in intestine.